H-shaped reinforced composite drainage network and preparation method thereof
By adopting the H-type reinforcement design in the composite drainage network, combined with the use of modified calcium sulfate whiskers and calcium carbonate, the problems of insufficient mechanical properties and poor anti-aging properties of the traditional composite drainage network are solved, and higher mechanical strength and service life are achieved.
Patent Information
- Application Number
- CN202510089833.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In actual applications, traditional composite drainage networks have problems such as insufficient mechanical properties and poor anti-aging properties, which leads to prone to deformation and damage when subjected to large loads, and are prone to oxidation and aging in natural environments for a long time, and shorten service life.
The design of the H-type enhanced composite drainage network is adopted. Through the composite structure of the mesh core and functional geotextile, combined with the enhancement and anti-aging effects of modified calcium sulfate whiskers, as well as the wear and compression resistance of calcium carbonate, the overall mechanical strength and service life of the composite drainage network are significantly improved.
It significantly improves the overall mechanical strength and service life of the composite drainage network, so that the product has excellent structural stability and durability, and can meet the long-term performance requirements in engineering applications.
Smart Images

Figure BDA0005251183010000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of drainage nets, and in particular to an H-shaped reinforced composite drainage net and a preparation method thereof. Background Art
[0002] Composite drainage net is an important geosynthetics material, which is widely used in drainage systems in highway, railway, water conservancy and other engineering construction. At present, the common composite drainage net is mainly composed of plastic drainage net core and geotextile, in which the net core provides drainage channel and the geotextile has filtering and protection function. As a new material to replace traditional sand mat and gravel layer, composite drainage net plays an important role in landfill, land-based reef tunnel and other projects, which can effectively drain the water between the foundation and the waste foundation and prevent the infiltration and diffusion of pollutants.
[0003] CN109137879A discloses a high-strength drainage net, including a drainage net core, wherein non-woven geotextiles are respectively provided on the upper and lower surfaces of the drainage net core, and the drainage net core comprises upper ribs, middle ribs and lower ribs, wherein the upper ribs and lower ribs are respectively located on the upper and lower end surfaces of the middle ribs, and the upper ribs, middle ribs and lower ribs are distributed at intervals, and the upper and lower end surfaces of the middle ribs are respectively provided with grooves for accommodating the upper ribs and the lower ribs, and the non-woven geotextile is bonded to the upper and lower surfaces of the drainage net core by an adhesive.
[0004] However, there are some urgent problems to be solved in the practical application of traditional composite drainage nets. On the one hand, the geotextile layer of the existing composite drainage net is generally made of a single polypropylene material. Although polypropylene material has good chemical stability and corrosion resistance, its mechanical properties are limited. It is easy to deform and damage when subjected to large loads, affecting the drainage effect; on the other hand, the polypropylene molecular structure does not contain anti-ultraviolet functional groups. Long-term exposure to the natural environment will cause ultraviolet radiation to cause oxidation and aging of the material, and the mechanical properties will decrease, greatly shortening the service life of the composite drainage net.
[0005] At present, domestic and foreign scholars' research on the modification of composite drainage nets mainly focuses on the optimization of the core structure and the modification of geotextiles. In terms of geotextile modification, commonly used methods include adding inorganic fillers, blending modification, etc., but these methods often have problems such as poor dispersibility and poor interface compatibility, and it is difficult to achieve the goals of improving mechanical properties and anti-aging properties at the same time. In particular, the traditional single-layer grid net structure is prone to mesh clogging, requiring frequent manual cleaning and maintenance, which greatly increases the cost of use. Therefore, it is of great practical significance to develop a composite drainage net product with excellent comprehensive performance. Summary of the invention
[0006] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide an H-type reinforced composite drainage net and a preparation method thereof. Through the composite structure design of the net core and the functionalized geotextile, combined with the reinforcement and anti-aging effects of modified calcium sulfate whiskers and the wear and compression resistance of calcium carbonate, the overall mechanical strength and service life of the composite drainage net are significantly improved, so that the product has excellent structural stability and durability, and can meet the long-term performance requirements in engineering applications.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] An H-shaped reinforced composite drainage net comprises a net core and geotextiles fixed on both sides of the net core. The geotextiles are made of the following components by weight: 90-120 parts of polypropylene, 4-12 parts of modified calcium sulfate whiskers, and 2-10 parts of calcium carbonate.
[0009] Preferably, the method for preparing the modified calcium sulfate whisker comprises the following steps:
[0010] (1) dispersing calcium sulfate whiskers in an ethanol aqueous solution, ultrasonically treating, adding 3-isocyanatepropyltriethoxysilane, heating and stirring, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0011] Silane coupling reaction: The ethoxy group of 3-isocyanatepropyltriethoxysilane is hydrolyzed in the presence of trace amounts of water to form silanol (-Si-OH), which then undergoes a condensation reaction with the hydroxyl groups on the whisker surface to form a Si-O-whisker covalent bond, while releasing ethanol. This process allows the whisker surface to obtain active isocyanate groups (-NCO), providing reaction sites for subsequent modification.
[0012] Preferably, in step (1), the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 85-95:15-5; the amount ratio of calcium sulfate whiskers, ethanol aqueous solution and 3-isocyanatepropyltriethoxysilane is 10g:100-150mL:0.5-3g.
[0013] Preferably, in step (1), the ultrasonic treatment is performed for 15 to 30 minutes; and the heating and stirring conditions are heating and stirring at 60 to 75° C. for 2 to 5 hours.
[0014] (2) dispersing the isocyanate-modified whiskers in DMF, ultrasonically treating, adding 4-hydroxycinnamic acid and dibutyltin dilaurate, stirring for reaction, centrifuging, washing, and drying the product to obtain cinnamic acid-modified whiskers;
[0015] Isocyanate-hydroxyl addition reaction: Under the catalysis of dibutyltin dilaurate, the isocyanate group (-NCO) on the surface of the whisker reacts with the hydroxyl group (-OH) of 4-hydroxycinnamic acid. The catalyst first forms an active intermediate with the isocyanate to increase the polarization degree of the C=N bond, and then the hydroxyl group attacks to form a carbamate bond (-NH-COO-), introducing the cinnamic acid group to the surface of the whisker and exposing a new carboxyl group (-COOH) on the surface.
[0016] Preferably, in step (2), the usage ratio of isocyanate-modified whisker, DMF, 4-hydroxycinnamic acid and dibutyltin dilaurate is 10 g: 100-150 mL: 0.5-2 g: 0.01-0.1 g.
[0017] Preferably, in step (2), the ultrasonic treatment is performed for 15 to 30 minutes; the stirring reaction conditions are 65 to 80° C. and the stirring reaction is performed for 5 to 8 hours; and the product is washed with DMF and acetone for 2 to 4 times in sequence.
[0018] (3) Dispersing the cinnamic acid modified whiskers in DMF, ultrasonically treating, adding DCC and NHS, stirring at room temperature for activation, then adding 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, heating and stirring for reaction, centrifuging, washing, and drying the product to obtain modified calcium sulfate whiskers.
[0019] Esterification grafting: The carboxyl groups on the whisker surface first react with DCC to form an O-acylurea intermediate, and NHS then attacks the intermediate to generate an active ester and releases a DCU byproduct. The activated ester group undergoes a nucleophilic substitution reaction with the hydroxyl group of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, connecting the UV absorber molecule to the whisker surface through an ester bond (-COO-), while releasing NHS.
[0020] Preferably, in step (3), the usage ratio of cinnamic acid modified whisker, DMF, DCC, NHS, and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is 10 g: 100-150 mL: 0.5-1 g: 0.25-0.5 g: 0.8-2.4 g.
[0021] Preferably, in step (3), the ultrasonic treatment is performed for 15 to 30 minutes; the stirring activation condition is stirring activation at room temperature for 30 to 60 minutes; the stirring reaction condition is stirring reaction at 65 to 80° C. for 4 to 7 hours; and the product is washed with DMF and acetone for 2 to 4 times in sequence.
[0022] The present invention also claims protection for a method for preparing the H-type reinforced composite drainage net, comprising the following steps: after the raw materials are evenly mixed, they are fed into a screw extruder, and after melting and extrusion, they are transferred to a spinning box, ejected from the spinneret holes of the spinning box, cooled by a side blower, and the cooled filament bundles are then air-drawn by a tubular stretcher to achieve uniform filament separation, and the filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow, and output to a needle punching machine via a pre-pressing roller, and the formed filament web is reinforced by pre-needling and main needling to obtain the geotextile; the geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0023] Preferably, the heating temperatures of each section of the screw extruder are 160° C., 180° C., 200° C., and 210° C., respectively, and the screw speed is 70 to 90 r / min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The H-type reinforced composite drainage net provided by the present invention adopts a composite structure of a mesh core and a geotextile, which improves the overall strength and stability of the drainage net. The modified calcium sulfate whiskers added to the geotextile provide a reinforcement effect through its needle-like structure with a high aspect ratio, while the surface modification imparts excellent interface compatibility and UV resistance; calcium carbonate can improve the wear resistance and compression resistance of the geotextile, and synergizes with the polypropylene matrix to significantly improve the mechanical properties and service life of the geotextile. In the preparation method, a screw extruder is used for melt extrusion, and the temperature and rotation speed of each section are precisely controlled to ensure the uniform dispersion of each component; the airflow drawing process is used to achieve uniform filament separation, and combined with the needle punching reinforcement process, the geotextile structure is made dense and uniform; finally, it is combined with the mesh core through an online hot composite process to ensure the composite interface bonding strength and improve the overall performance of the product.
[0026] 2. The present invention provides a modified calcium sulfate whisker, which significantly improves the comprehensive performance of the composite material. First, the calcium sulfate whisker itself has excellent mechanical properties, and its needle-like structure with a high aspect ratio (about 20 to 50) can form a three-dimensional network support structure in the polypropylene matrix, which significantly improves the tensile strength and modulus of the geotextile; secondly, the isocyanate group is introduced on the surface of the whisker by a silane coupling agent to form a molecular bridge, which effectively improves the interface compatibility and bonding strength between the whisker and the polypropylene matrix. Further, by grafting 4-hydroxycinnamic acid, a cinnamate structure with a high molar absorption coefficient is introduced, providing excellent ultraviolet light absorption capacity, and the unsaturated double bonds in its molecular structure may also provide additional interface interactions during processing. Finally, by introducing 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, a composite ultraviolet light absorption system is formed with the cinnamate structure, which can synergistically improve the anti-aging performance of the geotextile; at the same time, the introduction of the sulfonic acid group improves the hydrophilicity of the surface of the modified whisker, and this hydrophilic modification helps to improve the permeability of the geotextile. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0028] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0029] Polypropylene was purchased from Liaoning Huajin Tongda Chemical Co., Ltd., model T30S;
[0030] Calcium sulfate whiskers were purchased from Wanda Plastic Factory, Dongguan, Guangdong, with an average length of 50-200 μm, an average diameter of 1-5 μm, and an elastic modulus of 20.5 Gpa;
[0031] Calcium carbonate was purchased from Beijing Dekedaojin Technology Co., Ltd. with an average particle size of 20 nm.
[0032] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0033] (1) Dispersing 10 g of calcium sulfate whiskers into 100-150 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 85-95:15-5), ultrasonically treating for 15-30 min, adding 0.5-3 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 60-75° C. for 2-5 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0034] (2) dispersing 10 g of isocyanate-modified whiskers into 100-150 mL of DMF, ultrasonically treating for 15-30 min, adding 0.5-2 g of 4-hydroxycinnamic acid and 0.01-0.1 g of dibutyltin dilaurate, stirring and reacting at 65-80° C. for 5-8 h, centrifuging the product, washing with DMF and acetone for 2-4 times, and drying to obtain cinnamic acid-modified whiskers;
[0035] (3) Dispersing 10 g of cinnamic acid modified whiskers in 100-150 mL of DMF, ultrasonically treating for 15-30 min, adding 0.5-1 g of DCC and 0.25-0.5 g of NHS, stirring and activating at room temperature for 30-60 min, then adding 0.8-2.4 g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, heating to 65-80° C. and stirring for reaction for 4-7 h, centrifuging the product, washing with DMF and acetone for 2-4 times, and drying to obtain modified calcium sulfate whiskers;
[0036] (4) After 90-120 parts of polypropylene, 4-12 parts of modified calcium sulfate whiskers and 2-10 parts of calcium carbonate are uniformly mixed, the mixture is fed into a screw extruder. The heating temperatures of the various sections of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 70-90 r / min. After melting and extrusion, the mixture is transferred into a spinning manifold and ejected from the spinneret holes of the spinning manifold. The mixture is cooled by a side blower. The cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow, and are output to a needle punching machine via a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0037] The present invention will be further described below through specific embodiments.
[0038] Example 1
[0039] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0040] (1) Dispersing 10 g of calcium sulfate whiskers into 100 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 90:10), ultrasonically treating for 30 min, adding 3 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 75° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0041] (2) 10 g of isocyanate-modified whiskers were dispersed in 100 mL of DMF, and ultrasonically treated for 30 min. 2 g of 4-hydroxycinnamic acid and 0.1 g of dibutyltin dilaurate were added, and the mixture was stirred at 80° C. for 5 h. The product was centrifuged, washed three times with DMF and acetone, and dried to obtain cinnamic acid-modified whiskers.
[0042] (3) 10 g of cinnamic acid modified whiskers were dispersed in 100 mL of DMF, ultrasonically treated for 30 min, 1 g of DCC and 0.5 g of NHS were added, and the mixture was stirred and activated at room temperature for 45 min. Then, 2.4 g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid was added, and the mixture was heated to 80 ° C and stirred for 4 h. The product was centrifuged, washed with DMF and acetone three times in sequence, and dried to obtain modified calcium sulfate whiskers;
[0043] (4) After 1200 g of polypropylene, 120 g of modified calcium sulfate whiskers and 100 g of calcium carbonate are mixed evenly, the mixture is fed into a screw extruder. The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 80 r / min. After melting and extrusion, the mixture is transferred into a spinning box and ejected from the spinneret holes of the spinning box. The mixture is cooled by a side blower. The cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow, and are output to a needle punching machine via a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0044] Example 2
[0045] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0046] (1) Dispersing 10 g of calcium sulfate whiskers into 100 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 90:10), ultrasonically treating for 30 min, adding 2 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 70° C. for 3 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0047] (2) 10 g of isocyanate-modified whiskers were dispersed in 100 mL of DMF, and ultrasonically treated for 30 min. 1.5 g of 4-hydroxycinnamic acid and 0.07 g of dibutyltin dilaurate were added, and the mixture was stirred at 75° C. for 6 h. The product was centrifuged, washed three times with DMF and acetone, and dried to obtain cinnamic acid-modified whiskers.
[0048] (3) 10 g of cinnamic acid modified whiskers were dispersed in 100 mL of DMF, ultrasonically treated for 30 min, 0.8 g of DCC and 0.4 g of NHS were added, and the mixture was stirred and activated at room temperature for 45 min. Then, 2 g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid was added, and the mixture was heated to 75 °C and stirred for reaction for 5 h. The product was centrifuged, washed three times with DMF and acetone, and dried to obtain modified calcium sulfate whiskers.
[0049] (4) After 1100g of polypropylene, 100g of modified calcium sulfate whisker and 80g of calcium carbonate are mixed evenly, the mixture is fed into a screw extruder. The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 80r / min. After melting and extrusion, the mixture is transferred into a spinning box and ejected from the spinneret holes of the spinning box. The mixture is cooled by a side blower. The cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow, and are output to a needle punching machine through a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0050] Example 3
[0051] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0052] (1) Dispersing 10 g of calcium sulfate whiskers into 100 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 90:10), ultrasonically treating for 30 min, adding 1 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 65° C. for 4 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0053] (2) 10 g of isocyanate-modified whiskers were dispersed in 100 mL of DMF, and ultrasonically treated for 30 min. 1 g of 4-hydroxycinnamic acid and 0.04 g of dibutyltin dilaurate were added, and the mixture was stirred at 70° C. for 7 h. The product was centrifuged, washed three times with DMF and acetone, and dried to obtain cinnamic acid-modified whiskers.
[0054] (3) 10 g of cinnamic acid modified whiskers were dispersed in 100 mL of DMF, ultrasonically treated for 30 min, 0.7 g of DCC and 0.35 g of NHS were added, and the mixture was stirred and activated at room temperature for 45 min. Then, 1.4 g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid was added, and the mixture was heated to 70 ° C and stirred for 6 h. The product was centrifuged, washed with DMF and acetone three times in sequence, and dried to obtain modified calcium sulfate whiskers;
[0055] (4) 1000 g of polypropylene, 60 g of modified calcium sulfate whiskers and 40 g of calcium carbonate are mixed evenly and then fed into a screw extruder. The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 80 r / min. After melting and extrusion, the mixture is transferred to a spinning box and ejected from the spinneret holes of the spinning box. The mixture is cooled by a side blower and the cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow and output to a needle punching machine via a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0056] Example 4
[0057] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0058] (1) Dispersing 10 g of calcium sulfate whiskers into 100 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 90:10), ultrasonically treating for 30 min, adding 0.5 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 60° C. for 5 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0059] (2) 10 g of isocyanate-modified whiskers were dispersed in 100 mL of DMF, and ultrasonically treated for 30 min. 0.5 g of 4-hydroxycinnamic acid and 0.01 g of dibutyltin dilaurate were added, and the mixture was stirred at 65 °C for 8 h. The product was centrifuged, washed with DMF and acetone three times in sequence, and dried to obtain cinnamic acid-modified whiskers.
[0060] (3) 10 g of cinnamic acid modified whiskers were dispersed in 100 mL of DMF, and ultrasonically treated for 30 min. 0.5 g of DCC and 0.25 g of NHS were added, and the mixture was stirred and activated at room temperature for 45 min. Then 0.8 g of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid was added, and the mixture was heated to 65 ° C and stirred for 7 h. The product was centrifuged, washed with DMF and acetone three times in sequence, and dried to obtain modified calcium sulfate whiskers.
[0061] (4) 900 g of polypropylene, 40 g of modified calcium sulfate whiskers and 20 g of calcium carbonate are mixed evenly and then fed into a screw extruder. The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 80 r / min. After melting and extrusion, the mixture is transferred to a spinning box and ejected from the spinneret holes of the spinning box. The mixture is cooled by a side blower and the cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow and output to a needle punching machine via a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0062] Comparative Example 1
[0063] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0064] (1) Dispersing 10 g of calcium sulfate whiskers into 100 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 90:10), ultrasonically treating for 30 min, adding 3 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 75° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0065] (2) 10 g of isocyanate-modified whiskers were dispersed in 100 mL of DMF, and ultrasonically treated for 30 min. 2 g of 4-hydroxycinnamic acid and 0.1 g of dibutyltin dilaurate were added, and the mixture was stirred at 80° C. for 5 h. The product was centrifuged, washed three times with DMF and acetone, and dried to obtain cinnamic acid-modified whiskers.
[0066] (3) After 1200 g of polypropylene, 120 g of modified calcium sulfate whiskers and 100 g of calcium carbonate are mixed evenly, the mixture is fed into a screw extruder. The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 80 r / min. After melting and extrusion, the mixture is transferred into a spinning box and ejected from the spinneret holes of the spinning box. The mixture is cooled by a side blower. The cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow, and are output to a needle punching machine via a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0067] Comparative Example 2
[0068] A method for preparing an H-shaped reinforced composite drainage net comprises the following steps:
[0069] (1) Dispersing 10 g of calcium sulfate whiskers into 100 mL of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 90:10), ultrasonically treating for 30 min, adding 3 g of 3-isocyanatepropyltriethoxysilane, heating and stirring at 75° C. for 2 h, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers;
[0070] (2) 1200 g of polypropylene, 120 g of modified calcium sulfate whiskers and 100 g of calcium carbonate are mixed evenly and then fed into a screw extruder. The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C and 210°C respectively, and the screw speed is 80 r / min. After melting and extrusion, the mixture is transferred to a spinning box and ejected from the spinneret holes of the spinning box. The mixture is cooled by a side blower and the cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation. The filaments are evenly laid on a coagulation curtain under the control of a side-blowing airflow and output to a needle punching machine via a pre-pressing roller. The formed filament web is reinforced by pre-needling and main needling to obtain the geotextile. The geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
[0071] The geotextiles prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests. The tensile breaking strength of the geotextile was tested with reference to GB / T 3923.1-2013 "Tensile properties of textile fabrics Part 1: Determination of breaking strength and elongation at break (strip method)"; the tensile breaking strength of the geotextile was tested with reference to GB / T31899-2015 "Textile weathering test ultraviolet exposure", and the cumulative irradiation was 200 hours under 340nm wavelength ultraviolet lamp, and other experimental conditions referred to experimental condition 2 of the standard, and 7 cycles were repeated, and then the mechanical property retention rate of the geotextile was tested; the number of friction resistance was tested with reference to GB / T21196.2-2007 "Determination of abrasion resistance of textile fabrics by Martindale method Part 2: Determination of specimen damage"; the vertical permeability was tested with reference to GB / T 15789-2016 "Determination of vertical permeability characteristics of geotextiles and related products under no load"; the specific data are shown in Table 1.
[0072] Table 1 Geotextile performance test results
[0073]
[0074] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An H-shaped reinforced composite drainage net, comprising a net core and geotextiles fixed on both sides of the net core, characterized in that: The geotextile is made of the following components by weight: 90-120 parts of polypropylene, 4-12 parts of modified calcium sulfate whiskers, and 2-10 parts of calcium carbonate.
2. The H-type reinforced composite drainage net according to claim 1, characterized in that: The preparation method of the modified calcium sulfate whisker comprises the following steps: (1) dispersing calcium sulfate whiskers in an ethanol aqueous solution, ultrasonically treating, adding 3-isocyanatepropyltriethoxysilane, heating and stirring, filtering the product, washing with alcohol, and drying to obtain isocyanate-modified whiskers; (2) dispersing the isocyanate-modified whiskers in DMF, ultrasonically treating, adding 4-hydroxycinnamic acid and dibutyltin dilaurate, stirring for reaction, centrifuging, washing, and drying the product to obtain cinnamic acid-modified whiskers; (3) Dispersing the cinnamic acid modified whiskers in DMF, ultrasonically treating, adding DCC and NHS, stirring at room temperature for activation, then adding 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, heating and stirring for reaction, centrifuging, washing, and drying the product to obtain modified calcium sulfate whiskers.
3. The H-type reinforced composite drainage net according to claim 2, characterized in that: In step (1), the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 85-95:15-5; the amount ratio of calcium sulfate whisker, ethanol aqueous solution and 3-isocyanatepropyltriethoxysilane is 10g:100-150mL:0.5-3g.
4. The H-type reinforced composite drainage net according to claim 2, characterized in that: In step (1), the ultrasonic treatment is performed for 15 to 30 minutes; and the heating and stirring conditions are heating and stirring at 60 to 75° C. for 2 to 5 hours.
5. The H-type reinforced composite drainage net according to claim 2, characterized in that: In step (2), the usage ratio of isocyanate modified whisker, DMF, 4-hydroxycinnamic acid and dibutyltin dilaurate is 10 g: 100-150 mL: 0.5-2 g: 0.01-0.1 g.
6. The H-type reinforced composite drainage net according to claim 2, characterized in that: In step (2), the ultrasonic treatment is performed for 15 to 30 minutes; the stirring reaction condition is 65 to 80° C. and the stirring reaction is performed for 5 to 8 hours; the product is washed with DMF and acetone for 2 to 4 times in sequence.
7. The H-type reinforced composite drainage net according to claim 2, characterized in that: In step (3), the usage ratio of cinnamic acid modified whisker, DMF, DCC, NHS and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is 10 g: 100-150 mL: 0.5-1 g: 0.25-0.5 g: 0.8-2.4 g.
8. The H-type reinforced composite drainage net according to claim 2, characterized in that: In step (3), the ultrasonic treatment is performed for 15 to 30 minutes; the stirring activation condition is stirring activation at room temperature for 30 to 60 minutes; the stirring reaction condition is heating to 65 to 80° C. and stirring the reaction for 4 to 7 hours; the product is washed with DMF and acetone for 2 to 4 times in sequence.
9. A method for preparing the H-type reinforced composite drainage net according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: after the raw materials are evenly mixed, they are sent into a screw extruder, after melting and extrusion, they are transferred into a spinning box, ejected from the spinneret holes of the spinning box, cooled by a side blower, and the cooled filament bundles are then air-drawn by a tubular drawer to achieve uniform filament separation, the filaments are evenly laid on a coagulation curtain under the control of a side-blown airflow, output to a needle punching machine through a pre-pressing roller, and the formed filament web is reinforced by pre-needling and main needling to obtain the geotextile; the geotextile and the mesh core are prepared by online hot compounding to obtain the H-type reinforced composite drainage net.
10. The preparation method according to claim 9, characterized in that: The heating temperatures of each section of the screw extruder are 160°C, 180°C, 200°C, and 210°C, respectively, and the screw speed is 70-90r / min.
Citation Information
Patent Citations
High-strength drainage network
CN109137879A
Preparation method of modified calcium sulfate whisker-doped sodium polyacrylate composite material
CN109942740A
Self-reinforced polypropylene composite plastic geotextile and preparation method thereof
CN110747582A
Calcium sulfate whisker reinforced polypropylene and preparation method thereof
CN116970242A
Composite three-rib filtering enhanced drainage network
CN214363417U